The Structure of Texts from Herbalist-Client Encounters in Yoruba Traditional Medicine - Adegbite, Wale (2014)
Using data from Yoruba therapeutic communication, this paper describes the structure of texts from herbalist-client encounters in the practice of Yoruba traditional medicine. The study reveals, among other things, that some Yoruba traditional medicine texts have solely dialogical structures which are constituted by diagnostic and prescriptive transactions, while some others combine the dialogical structures above with monological narratives, descriptions, arguments and requests made in divinatory, incantatory and supplicating transactions. It also reveals that the herbalist controls the interaction in the practice of Yoruba traditional medicine and takes very long turns which are used mainly to give information and directives to clients in the practice.